The Methodology of the Development of the Worldview of Schoolchildren through Games - Nurgul Shadiyeva3, Rakhat Yelubayeva4Аlmagul Аkazhanova1, Saule Nurgali2, Meruyert Alibayeva2 (Opción, 2019)
The aim of the study is to investigate the methodology of the development of the worldview of schoolchildren through games via comparative qualitative research methods. As a result, proper and highquality use of national games in the field of education depends on the exact definition of their place and duty at each period of lessons and goals. In conclusion, the duty of every teacher is to enlighten the centuries-old national heritage of our country through training and education, to promote forgotten traditions and national identity, and to form among them the national psychology.